Knowledge sharing processes with the participation of key employees = Procesy dzielenia się wiedzą z udziałem pracowników kluczowych - Morawski, Mieczysław (Zielona Góra: Faculty of Economics and Management Press)
The fundamental of the most important problems of human capital management, especially in relation to knowledge management is theoretical research and application verification conditions, motives and methods to encourage key employees of companies to communicate the knowledge of low-skilled workers. Key personnel represent top-class professionals. They include top managers, senior executives of long-term employment in a company and specialists presenting unique knowledge and skills. The Author presents research findings based on questionnaire surveys made up of a sample consisting of fifty companies operating in Poland.
Keywords: pracownik kluczowy; dzielenie się wiedzą; motywowanie pracowników kluczowych; kapitał ludzki; key employee; knowledge sharing; key employees motivating; human capital